Type A and AB thymomas: histological features associated with increased stage - Green, Anna C.; Marx, Alexander; Ströbel, Philipp (Histopathology, 2015)
Aims The current WHO classification of thymic epithelial neoplasms describes type A and type AB thymomas as behaving ‘like benign neoplasms’. However, recent published data suggest that rare cases may show more aggressive behaviour. The aim of this study was to assess the frequency of atypical cases, and to determine whether atypia is associated with more advanced disease. Methods and results One hundred and twenty-one thymomas (type A, n = 68; type AB, n = 53) were retrospectively reviewed for ‘atypical’ features (nuclear pleomorphism, mitotic activity, and necrosis). Logistic regression was used to ascertain the association with increasing Masaoka-Koga stage. Where available, follow-up data were also reviewed. There were 72 stage I, 42 stage II, five stage III and two stage IV tumours. Only the presence of necrosis showed a significant association with increased stage in univariate and multivariate analysis. Nuclear atypia and increased mitotic activity were not associated with increasing stage of disease. Conclusions Our data support the concept of there being more aggressive atypical variants of both type A and type AB thymoma, and suggest that the presence of necrosis could be used to predict aggressive behaviour.